Optimization of grape artificial hybrid pollination technology process and the effect of different male parents on the fruit setting rate - Zhou, Ruijin; Gai, Ruxin; Liao, Wanying; Wu, Qiujie; Cheng, Jiahui; Li, Yongmu; Fan, Xiucai; Li, Guirong (Frontiers in Plant Science, 2025)
Grape (Vitis vinifera L.) is a globally paramount fruit crop, exerting a pivotal role in China’s agricultural production. However, the grape industry confronts core bottlenecks: centralized table grape listing resulting in recurrent oversupply, underdeveloped independent brand development, scarcity of internationally recognized cultivars, and suboptimal crossbreeding efficiency (e.g., concentrated 6 - 10-day flowering periods, complex flower ear structures, and stringent technical requirements for emasculation/pollination). To tackle these industry and breeding challenges, this study refined artificial hybridization pollination protocols and systematically analyzed pollen viability and hybridization affinity of nine male parents, using ‘Shine Muscat’ (Vitis labrusca × Vitis vinifera) grape as the female parent. Key findings revealed that pollen collection 1–2 days before messenger flower bloom optimizes viability, Ultra-low -80°C storage sustained pollen viability optimally. Precise early-stage anther removal and three-day pollination post stigma mucus secretion elevate the fruit set rate by 15%–20%. Hybrid combinations exhibited significant variations in fruit set rate (27.8%–62.3%), with ‘Moldova’ grape achieving the highest rate of 62.3%. A standardized process integrating parental selection, pollen management, emasculation-pollination, and data recording was established, elevating hybridization success rates by over 40%. This study delivers a scalable solution for grape cultivation.